Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1101/2021.06.27.450080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Candida albicans Isolates 529L and CHN1 Exhibit Stable Colonization of the Murine Gastrointestinal Tract

Abstract: Candida albicans is a pathobiont that colonizes multiple niches in the body including the gastrointestinal (GI) tract, but is also responsible for both mucosal and systemic infections. Despite its prevalence as a human commensal, the murine GI tract is generally refractory to colonization with the C. albicans reference isolate SC5314. Here, we identify two C. albicans isolates, 529L and CHN1, that stably colonize the murine GI tract in three different animal facilities under conditions where SC5314 is lost fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The five slowest-growing strains originated from five different hosts and showed significantly decreased growth rate and saturating density relative to other isolates from the same host. Although the five slowest-growing isolates were all obtained from oral samples, we did not observe a significant difference in growth rate between oral and fecal samples As filamentation has been tightly associated with virulence, and because previous work in murine models has suggested that gut adapted strains may lose their ability to filament [20,34,36], we examined each isolate in the collection for their ability to form hyphae using 10% serum and febrile temperatures as two inducing cues.…”
Section: Results: Phenotypic Characterization Of Commensal C Albicans...mentioning
confidence: 72%
See 4 more Smart Citations
“…The five slowest-growing strains originated from five different hosts and showed significantly decreased growth rate and saturating density relative to other isolates from the same host. Although the five slowest-growing isolates were all obtained from oral samples, we did not observe a significant difference in growth rate between oral and fecal samples As filamentation has been tightly associated with virulence, and because previous work in murine models has suggested that gut adapted strains may lose their ability to filament [20,34,36], we examined each isolate in the collection for their ability to form hyphae using 10% serum and febrile temperatures as two inducing cues.…”
Section: Results: Phenotypic Characterization Of Commensal C Albicans...mentioning
confidence: 72%
“…We then performed growth assays on all 910 isolates and the SC5314 reference strain in rich medium (yeast peptone) with dextrose, galactose, or glycerol as the carbon source. We observed unimodal distributions with a long tail of slow-growing strains for both exponential growth (µ max ) and saturating density (K) in rich media (Fig 1C As filamentation has been tightly associated with virulence, and because previous work in murine models has suggested that gut adapted strains may lose their ability to filament [20,34,36], we examined each isolate in the collection for their ability to form hyphae using 10% serum and febrile temperatures as two inducing cues.…”
Section: Results: Phenotypic Characterization Of Commensal C Albicans...mentioning
confidence: 96%
See 3 more Smart Citations